2018
DOI: 10.1080/02786826.2018.1514101
|View full text |Cite
|
Sign up to set email alerts
|

A review of transfer theory and characterization of measured performance for differential mobility analyzers

Abstract: Particle transfer theory for steady-state differential mobility analyzers (DMAs) with and without diffusion is reviewed in detail with a particular focus on the assumptions and approximations made in the analysis. Impacts of the approximations are discussed and, where available, methods to reduce the errors of these approximations are suggested. The nondiffusing theory uses just one approximation, affecting the centroid calculation, which can be readily addressed via numerical modeling of the electric field. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
1
22
0
3
Order By: Relevance
“…The empirical transfer functions and the penetration efficiencies of the half-mini DMAs were analyzed using the data inversion routine presented in Jiang et al (2011c) and Cai et al (2017) with updates reported by Stolzenburg (2018). The corrected ratio of the aerosol concentrations recorded by the two FCEs, N 2/N1, is equal to the product of penetration efficiency and transfer function:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The empirical transfer functions and the penetration efficiencies of the half-mini DMAs were analyzed using the data inversion routine presented in Jiang et al (2011c) and Cai et al (2017) with updates reported by Stolzenburg (2018). The corrected ratio of the aerosol concentrations recorded by the two FCEs, N 2/N1, is equal to the product of penetration efficiency and transfer function:…”
Section: Methodsmentioning
confidence: 99%
“…The DMA transfer function used in this study is a diffusing transfer function (Stolzenburg 1988;Stolzenburg and McMurry 2008;Stolzenburg 2018):…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the evaluation of the M Ã i integrals, the diffusing form of the transfer function (Stolzenburg and McMurry 2008;Stolzenburg 2018;and Equation (S2) of the online supplementary information [SI]) is used, dependent on Z p , fixed flow ratios b and d, and the dimensionless diffusion parameter s. The lengthy derivation of these moments is set forth in the SI and results in…”
Section: Evaluation Of the M I ã And P K ã Integralsmentioning
confidence: 99%